PENGARUH BEBAN OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO) DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP RETURN ON ASSETS (ROA) PADA BANK UMUM KONVENSIONAL PERIODE 2016-2022 - Budiman, Ervina Aulia; Nasution, Raden (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to ascertain how operational costs affect operating income (BOPO) and capital adequacy ratio (CAR) affect return on assets (ROA) for traditional commercial banks listed on the Indonesia Stock Exchange (IDX) for the years 2016 through 2022. Conventional banks that are listed on the IDX from 2016 to 2022 make up the study's population. Based on established criteria, a total sample of seven companies was selected in this study. Data analysis was done using multiple regression analysis, the traditional assumption test, and descriptive statistical analysis. The results of this study show that (1) Operating Expenses Against Operating Income (BOPO) (X1) have a negative effect on Return On Assets (ROA). This is indicated by a significance value (Sig.) 0.000 <0.050. (2) Capital Adequacy Ratio (CAR) (X2) has no significant effect on Return On Assets (ROA). This is indicated by a significance value (Sig.) 0.390 > 0.050. (3) Operating Expenses to Operating Income (BOPO) (X1) and Capital Adequacy Ratio (CAR) (X2) have a simultaneous effect on Return On Assets (ROA). This is indicated by a significance value (Sig.) 0.000< 0.05.